Diferentes meios de cultivo e condições operacionais na produção de penicilina G acilase por Bacillus megaterium - Souza, Vanessa Ribeiro de (2007)
Penicillin G acylase (PGA) is an important enzyme for industry, used to produce aminopenicillanic acid, a key intermediate in the synthesis of ampicillin, among other betalatam antibiotics. The production of this enzyme by Bacillus megaterium has been studied by the research group for several years. This work advances this research, aiming not only at the enhancement of the enzyme production, but also at a better understanding of B. megaterium regulatory expression mechanisms for PGA. A systematic study of the inoculum, including conservation strategies for the microorganism, was performed. Different cultivation media and operational conditions for the production of PGA were investigated, especially temperature and dissolved oxygen concentration. Enzyme recovery was also studied, including methodologies for minimizing protein contents in whey. Cheese whey is an important nutrient for enzyme production, but its use implies the presence of contaminant proteins in the culture broth. Finally, the enzyme was kinetically characterized. During the inoculum study, PGA yields of microorganisms conserved using different techniques were compared: endospores in 20%-glycerol, -50oC (cryotubes), endospores in solid medium, in refrigerator ( slants ) and vegetative cells in 5%-glycerol, -50oC ( eppendorffs ). It was observed that cryotubes (frozen spores) preserve the enzyme production levels for 12 months, 521 IU/L ±20 IU/L with great reproducibility. Conservation in slants shows a marked fall of production after one month, with a low reproducibility along months. Freezing vegetative cells leads to the highest patterns of enzyme production, up to 900 IU/L, but preservation is sustained for only five months. Maximum specific growth rates changed according to the conservation method, with µmax eppendofor > cryotube > slant . A study of the effect of the inoculum growth period on enzyme yield has shown that, for the three conservation methods, harvesting between 8 and 12 h leaded to similar cell mass and enzyme concentrations after 24 h of cultivation. The procedure of harvesting the inoculum after 12 h, with 10%-bioreactor inoculum volume, showed to be a good method for inoculum standardization. The effect of temperature on the cultivation of B. megaterium for production of PGA was assessed in the range 24-40oC. Maximum cell concentration and maximum enzyme yield were achieved at 30oC. The effect of the concentration of dissolved oxygen on the production of PGA was studied, using air to feed the bioreactor (culture medium volume: 1.2-2.0 L). A second B. megaterium strain showed a lower growth rate than the original one, demanding 24 h for germination/propagation, while the original one requires 12 h. Thus, different oxygen (air) feeding strategies were tested for both strains. Along the years, enzyme yields in agitated flasks have been higher than in bioreactor, for almost all assays. For the second strain, sustaining the dissolved oxygen at 10% of saturation leaded to the highest enzyme productivity among all tested conditions, with a bioreactor productivity similar to the agitated flasks. For the original strain a similar production was only achieved with an increasing stirring profile, implying a very low dissolved oxygen concentration, equal to zero during long periods of the cultivation. The two strains presented different dissolved oxygen requirements. Changes in the cultivation medium also implied different dissolved oxygen requirements for a maximum enzyme yield. Cheese whey has a still no-identified substance that is an essential nutrient for enzyme production. The use of enzymatically hydrolyzed cheese whey improves the downstream process. Assays in agitated flasks, with the original strain, using hydrolyzed whey, leaded to PGA levels similar to the ones obtained using integral whey. However, in bioreactor the yield of enzyme was always lower than in agitated flasks, no matter the aeration strategy that was used. Three possible explanations for this fact were investigated: 1) microorganism preservation method; 2) changes in the time necessary for attaining and sustaining the metabolic state where enzyme expression occurs, what could be related to the ratio between vegetative cells and spores along time, in flasks and in the bioreactor; 3) increase in the production of proteases in the bioreactor, compared to the flasks. The lower yield using hydrolyzed whey does not seem to be related to none of these hypotheses, and up to now it was not possible to generalize the study of the effect of this variable on the PGA production by B. megaterium. Enzyme purification and concentration, via ultra-diafiltration, in the presence of integral and hydrolyzed whey was another subject for research. The effect of pH and of the number of washing cycles on enzyme recovery was assessed. Results showed that this technique is efficient, provided it is run at low temperatures. Hydrolyzed whey indeed eases the purification of the enzyme using membranes, and great part of the contaminant whey proteins can be removed. However, an expressive loss of PGA occurs during the diafiltration stages, which must be minimized. pH did not influence enzyme recovery. The kinetic characterization of the produced enzyme, using the hydrolysis of penicillin G as standard reaction, has showed that maximum PGA activity is at pH 8 and 37oC. Estimated Michelis-Menten parameters were Vmax= 0.0344 mMPenG/min and Km=1.83 mM, with activation energy equal to 27.12 KJ/mol.